Congenital Ulcerated Lip Hemangioma Treated with a Cleft Lip Technique. (March 2017) - Bianchi, Alberto; Amadori, Sara; Bassi, Massimo; Neri, Iria; Campobassi, Angelo; Marchetti, Claudio
A neonate presented to our clinic for evaluation of unusual congenital cleft lip. The clinical follow-up showed at first an ulceration of the lesion and then a stable result after propanolol systemic therapy. After 18 months of clinical follow-up, surgical treatment was performed, which consisted of double unilimb Z-plasty according to Mulliken's microform cleft lip repair. Knowing the existence of these strange vascular anomalies of the lip will allow us to improve the differential diagnosis and treatment plan.